DUAL ROLE CONFLICT, COPING STRESS, AND SOCIAL SUPPORT AS NURSES’ WELL-BEING PREDICTOR - Widyasrini, Jati Uji Sekti; Lestari, Sri (Jurnal Psikologi, 2020)
Nurses' well-being is one of the essential factors in achieving happiness. Conflict and stress experienced by the nurse can make the nurse feel the lack of well-being in her life. This study examines dual role conflict, coping stress, and social support as the predictor of nurses' well-being. The respondents of this study were 123 nurses who were obtained through random cluster sampling. The data were collected using four scales: life well-being scale, dual role conflict scale, coping stress scale, and social support scale. Data analysis was done by conducting linear regression. The results show that dual role conflict, coping with stress, and social support can predict nurses' well-being. Dual role conflict, coping with stress, and social support accounted for 27.5% of the nurses' well-being. Social support is the strongest predictor, followed by coping stress and dual role conflict. This research implies that providing adequate social support from both family and co-workers can facilitate the nurses to achieve their well-being. Besides, it is essential to improve the nurses' skills in managing stress so they can balance the coping strategies and handle the dual role conflict constructively. Receiving plenty of social support will encourage the nurse to choose appropriate coping strategies to manage the dual role conflict constructively.